CONTENTS OF THE TECHNOLOGY FOR SIMULATING THE OPERATIONAL SERVICE ACTIVITIES OF THE BORDER GUARD IN THE CONDITIONS OF EMERGENCY SITUATIONS OF A TECHNOLOGICAL CHARACTER DURING A SPECIAL PERIOD - Polonchuk, Vasyl; Mazur, Valentyn (Honor and Law, 2023)
Modern society is experiencing changes, the causes of which are global transformations in the geopolitical, economic, technological, information and communication spheres and are tangential to every social institution. Mainly according to all social indicators of civilizational development, Ukraine continues to be on a dangerous border. Domestic scientists and practitioners believe that overcoming the systemic crisis in Ukraine is possible through the reformatting of society. Successful modernization is the basis of the dynamic and democratic progress of the state. Such a situation necessitates the revision of goals, adjustment and clarification of social development priorities, the need to form new, modern approaches to ensuring social security and, above all, social protection of the population. The purpose of the study was to analyse the content of modelling in the security and defence sector for Ukrainian society. The infrastructure of socio-economic and military potential of Ukraine, the aging of material and technical equipment in almost all spheres of society, as well as physical and geographical features of Ukraine pose a potential threat of unforeseen occurrence and increase in large-scale disasters with significant human casualties. The article analyses the problem of applying the method of modelling the operational and service activities of the border detachment in the conditions of a man-made situation during a special period. The study revealed the following: modelling is an advanced method of optimizing the operational and service activities of the border detachment in peacetime and wartime, the essence of the concepts of modelling and emergency. The content analysed above of the simulation of the operational-service activity of the border detachment in the conditions of a man-made emergency in a special period allows to ensure a high level of border security and the quality of operational-service activity at a professional level that meets the demands of modern society. Prospects for further scientific research may be as follows: analysis of foreign experience in the use of modelling technology in the activities of security and defence sector formations in the conditions of a man-made emergency, analysis of the effectiveness of the designed models of operational and service activities of the border detachment in the conditions of a man-made emergency.